2000
DOI: 10.1128/jb.182.20.5737-5748.2000
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Expression of HmuR, a TonB-Dependent Hemoglobin Receptor of Porphyromonas gingivalis

Abstract: The gram-negative pathogen Porphyromonas gingivalis requires hemin for growth. Hemoglobin bound to haptoglobin and hemin complexed to hemopexin can be used as heme sources, indicating that P. gingivalis must have a means to remove the hemin from these host iron-binding proteins. However, the specific mechanisms utilized by P. gingivalis for the extraction of heme from heme-binding proteins and for iron transport are poorly understood. In this study we have determined that a newly identified TonB-dependent hemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
170
1
4

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(192 citation statements)
references
References 44 publications
13
170
1
4
Order By: Relevance
“…1c, underlined sequence) than its previously reported variants (Karunakaran et al, 1997;Simpson et al, 2000). Also, the originally described HmuY led to incorrect annotation of the hmuY gene on the genome of P. gingivalis W83 at both Oralgen (http://www.oralgen.…”
Section: Analysis Of Hmuyrstuv Indicates That It Is a Novel Haemin-upmentioning
confidence: 96%
See 1 more Smart Citation
“…1c, underlined sequence) than its previously reported variants (Karunakaran et al, 1997;Simpson et al, 2000). Also, the originally described HmuY led to incorrect annotation of the hmuY gene on the genome of P. gingivalis W83 at both Oralgen (http://www.oralgen.…”
Section: Analysis Of Hmuyrstuv Indicates That It Is a Novel Haemin-upmentioning
confidence: 96%
“…The two genes were independently transcribed, and while hemR was repressed by haemin, orf1 was upregulated in the presence of haemin. Using a different P. gingivalis strain, A7436, Simpson et al (2000) demonstrated the presence of a homologue of this locus consisting of hmuY (99 % identical to orf1) and hmuR (identical at the 59 end to hemR but differing significantly at the 39 end). hmuY and hmuR are co-transcribed and repressed by iron.…”
Section: Introductionmentioning
confidence: 99%
“…Examples include hmuR and feoB-1 and -2. The hmuR (PG1552) gene encodes a TonBdependent outer membrane haemin utilization transporter, which is known to be regulated by iron levels and which possesses a Fur (ferric uptake regulator; PG0465) binding site in its promoter region (Simpson et al, 2000). The feoB-1 (PG1043) gene encodes an inner membrane ferrous iron uptake protein that is essential for pathogenesis of P. gingivalis and is also thought to be Fur-dependent (Dashper et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The molecular mechanisms underlying iron uptake have been extensively studied (Olczak et al, 2005). Genes involved in iron acquisition include the hmuYRSTUV locus (PG1551-PG1556), which encodes a novel hybrid haemin-uptake system (Brunner et al, 2010;Lewis et al, 2006;Olczak et al, 2005Olczak et al, , 2008Simpson et al, 2000Simpson et al, , 2004Smalley et al, 2011); the hbp35 gene (PG0616), which encodes a haemin-binding protein that also exhibits thioredoxin activity (Hiratsuka et al, 2010;Shoji et al, 2010); the surface protein HusA (PG2227), which acts as a haemophore with very high affinity (Gao et al, 2010); the tlr (PG0644) iron transport locus Slakeski et al, 2000); the haemin-binding protein FetB (PG0669) and the surrounding genes in that locus; and PG0465, the ferric uptake regulator (fur) (Olczak et al, 2005). In addition, regulatory mechanisms controlling expression of iron acquisition genes have been identified, including the transcriptional activator encoded by PG1237, which has been shown to control expression of the hmu locus (Wu et al, 2009).…”
Section: Discussionmentioning
confidence: 99%